Special athletic leadership award - De La Salle University, Manila (Animo Repository, 1990)
Grace Gaerlan and Jose Miguel Santamaria were recipients of the Special Athletic Leadership Award during the Commencement Exercises, Third Trimester SY 1989-1990.